The Swiss Vote on Limiting Second Homes - Martin Schuler; Pierre Dessemontet (Revue de Géographie Alpine)
The Alps have an important role in defining the Swiss national identity, and play a major part in forging the country’s image from the beginning of tourism in the 18th and 19th centuries. In a federalist country which assigns large decision powers to the cantonal and communal levels, local and national interests as to how to develop this particular space can profoundly diverge. The vote held on March 11th, 2012 on the Franz Weber initiative introducing a ban on building new holiday residences in touristic communes was a blatant example of such an opposition. The success of the initiative, albeit with a tiny majority, was a great shock; its territorial imprint was evident, drawing a line between alpine and prealpine cantons on one side, and mainland cantons on the other side. This paper proposes a spatial analysis of this vote and put it in context through a historical perspective. Indeed, of all the votes held since 1950 with an environmental or landscape component, we can find only one with the same territorial pattern – in 1965, “against inflation in the building industry” – as the 2012 vote. In all the other votes held on those subjects, other splits – linguistic, religious, or regional – manifested themselves, allowing the alpine populations to find allies. This paper asks thus the question as to whether the long-lived solidarity of mainland Switzerland with the Alps tends to dissipate.